2008
DOI: 10.1080/03630260701798375
|View full text |Cite
|
Sign up to set email alerts
|

A +8 (C→T) Mutation within the 5′ Untranslated Region of β-Globin Down-Regulates the mRNA Transcription

Abstract: The 5' untranslated region (5'UTR) of beta-globin has been well characterized and is often used as a model for eukaryotic transcription/translation, but there are still questions regarding the mechanism of translational control. Mutations affecting the Cap site at + 1 and at positions +10, +22, +33 and +40-43 have been described, and it is thought that the initiator element required for transcription stretches from -2 to +7 relative to the Cap site with a downstream element situated from +10 to +15. The influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Mutations in 5 0 UTRs have previously been found to modulate translation and even to cause disease; e.g., in hereditary hypotrichosis and familial thrombocytosis. [39][40][41] We show herein that the autosomal-recessive skin disorder KLICK syndrome is associated with a single-nucleotide deletion located in the 5 0 region of POMP and that the deletion is included in a proportion of POMP transcripts. Analysis of POMP mRNA in keratinocytes revealed that the deletion causes increased amounts of longer POMP transcripts, especially in in vitro differentiated keratinocytes.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…Mutations in 5 0 UTRs have previously been found to modulate translation and even to cause disease; e.g., in hereditary hypotrichosis and familial thrombocytosis. [39][40][41] We show herein that the autosomal-recessive skin disorder KLICK syndrome is associated with a single-nucleotide deletion located in the 5 0 region of POMP and that the deletion is included in a proportion of POMP transcripts. Analysis of POMP mRNA in keratinocytes revealed that the deletion causes increased amounts of longer POMP transcripts, especially in in vitro differentiated keratinocytes.…”
mentioning
confidence: 74%
“…Possible explanations are that the single-nucleotide deletion stabilizes the long 5 0 UTR POMP transcript by protecting it from degradation and/or that it increases the preferences of the preinitiation complex for an upstream TSS. [40][41][42] The observed lower translation efficiency of POMP transcripts with longer 5 0 UTRs would result in reduced levels of POMP and subsequently in reduced levels of mature proteasomes. We also observed an aberrant expression of POMP and a deviant distribution of a7 and b5 subunits by IHC in the terminal epidermal differentiation of KLICK patients, which coincides with an increased expression of the ER stress marker CHOP.…”
mentioning
confidence: 99%